2021
DOI: 10.1007/s10612-021-09562-4
|View full text |Cite
|
Sign up to set email alerts
|

Plastic Waste and the Environmental Crisis Industry

Abstract: Our relationship with plastic is complex. While the societal benefits of plastic are undeniable, plastic has also come to occupy a central role within a culture of waste and disposable living that constitutes a significant problem for health and the natural environment. Public awareness of the harms asociated with plastic is high, thanks, in part, to a range of sustained media exposure. This, however, has so far failed to materialize in any significant global reduction in plastic pollution. Meaningful regulato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The world’s production processes have historically relied on linear economies in which raw materials are processed into manufactured goods that are later discarded as waste. Consumer plastics are emblematic of the negative aspects of this model; they are sourced from unsustainable fossil resources and their resistance to decay and poor waste management pose threats to the environment. , It was estimated that over 359 million tons of plastics were produced globally in 2018, and this number is projected to grow at a rate of 3% annually . Less than 10% of the total plastic ever produced has been recycled, with the majority of the plastic waste either landfilled or released into the environment .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The world’s production processes have historically relied on linear economies in which raw materials are processed into manufactured goods that are later discarded as waste. Consumer plastics are emblematic of the negative aspects of this model; they are sourced from unsustainable fossil resources and their resistance to decay and poor waste management pose threats to the environment. , It was estimated that over 359 million tons of plastics were produced globally in 2018, and this number is projected to grow at a rate of 3% annually . Less than 10% of the total plastic ever produced has been recycled, with the majority of the plastic waste either landfilled or released into the environment .…”
Section: Introductionmentioning
confidence: 99%
“…Less than 10% of the total plastic ever produced has been recycled, with the majority of the plastic waste either landfilled or released into the environment . Microplastics disperse into marine environments, cause adverse effects throughout the ecosystem and food chain, and eventually induce potential health threats to the human population. , In efforts to alleviate environmental strain and improve resource efficiency, there has been increasing interest in a transition to a circular economy, which is rooted in the reuse and recycling of waste materials into intermediates that are practically identical to virgin starting materials and can be remanufactured and reprocessed …”
Section: Introductionmentioning
confidence: 99%
“…In addition to grey hydrogen, given the decrease in demand for coal and oil following the carbon tax, fossil fuel companies are marketing the use of plastics (The Story of Plastic 2019 ). As reported, plastics present an opportunity for big oil corporations to keep up demand (The Story of Plastic 2019 ), leading to a whole new range of harms attributed to plastic pollution (see Smith and Brisman 2021 ). Thus, fossil fuels are finding a new form and place to flow through the economy in the form of plastics and hydrogen, damaging the climate and environment even further.…”
Section: The ‘Revolving Doors’ a Legal Wrongdoingmentioning
confidence: 99%
“…While some respondents assumed these were fake environmentally friendly products, others claimed that this was probably a marketing strategy. In another study, participants argued that the solution to plastic waste and environmental disaster was initiating pseudo-individualized green products by many corporations [59]. Furthermore, studies have indicated that the price sensitivity of green products undermined the environmental impact on the green consumption objective [35,60,61].…”
Section: Environmental Consciousness When Buying Goodsmentioning
confidence: 99%